A Study Of Aluminium Window Frames Preference Materials Among Property Buyers - Mustakim, Ainaa Shafirah (Universiti Sains Malaysia, 2022)
The characteristics of the frame materials have significant impacts on the properties of a window. A window itself plays a crucial role in determining the overall energy performance of the building. This study analyses frame types of aluminium. Letting light into a cave or crude structure allowed its inhabitants to better perform tasks and navigate their surroundings, alerting them to the day’s cycle and keeping them in sync with it something that we understand is vital to human health and emotional health and wellbeing. Aluminium window frames are valued for their slim profile but durability, along with their low maintenance and strength. Due to their lightweight construction and strength, aluminium window frames are able to be configured in a variety of ways. This makes them beneficial for multi-panel systems or large windows. However, aluminium frames are not recommended in wet areas or areas that have high levels of salty water and air due to their corrosion. There was a time when choosing the right window frames meant you had to make a trade-off between strength and aesthetics. If you wanted a more resilient, stronger frame, you would almost always be presented with a bulky exterior. Well, that was until aluminium frame windows appeared on the scene. In no time, aluminium has climbed popularity charts in interior design and is now one of the most preferred materials for window frames. In fact, aluminium frame windows are just perfect for giving your personal spaces a facelift with a sleek, neat look.